PENGARUH CAIRAN ALUMINIZING TERHADAP KEKERASAN KAWAT BAJA - N, Dwi Putranto; Prayitno, Dody (P3M Politeknik Negeri Indramayu, 2017)
Wire rope is made from several steel wires a combined form a strand, a couple of strands twisted around the core to form a steel rope. One example of its usage is on the bridge to provide support for a heavy load. The steel wire is composed of several parts that is, steel wire, core and wire strand. Increasing the hardness of steel wire have the impact, the hardness of the steel wire. In an effort to improve the hardness of steel wire, there are opportunities to increase the hardness of steel wire with aluminizing method. The aim of this research is to find out the hardness of Wire in aluminizing process with alloys Al - Cu - Sn. Moreover to the research also aims to focus on the addition of Sn element in Al - Cu liquid. The methodology research was preceded by spliting wires from the wire rope. After that cut the wire into the sample wire. Then soak the wire into Al - Cu – Sn liquid at a temperature of 700ºC for ± 3 minutes. Elements of Sn which contained in the composition of Al - Cu - Sn vary from 0 % , 10 % and 20 % , while for CU’s component is 10 % and the rest of is Al, and the latter only elements of Al - Sn, without adding Cu element. Wire samples were then take away and cooled at room temperature, then test the wire by using micro hardness test, the test data was analyzed with Anova and finally made a conclusion. The results of this of this research showed that for the violence that occurs in the intermetallic layer shows the increase in value of hardness obtained on steel wire.